Strategy and development of organizations in the management of public administration - Cichoń, Seweryn; Knop, Urszula (Management and Administration Journal, 2019)
The development has an overarching character as a concept for creating strategic objectives and priorities for the organization in public administration. The important role of strategy is well known, both in traditional and modern management. The development strategy of the organization in the meaning of public administration takes into account the use of knowledge to analyze current and future activities and predicting the possibility of changes occurring in the environment. Knowledge of human resources management, improvement of methods and tools, enhances the effects of work organization, relationships and promotes the implementation of previously assumed strategic tasks. Continuous development in the activity of public institutions also affects the external evaluation and contributes to improving the quality of provided services.